A Multifunctional Self‐Assembled Monolayer for Highly Luminescent Pure‐Blue Quasi‐2D Perovskite Light‐Emitting Diodes (Advanced Optical Materials 20/2022). Issue 20 (18th October 2022) - Shin, Yun Seop; Ameen, Shahid; Oleiki, Elham; Yeop, Jiwoo; Lee, Youngwan; Javaid, Saqib; Park, Chan Beom; Song, Taehee; Yuk, Dohun; Jang, Hyungsu; Yoon, Yung Jin; Lee, Woojin; et al.
Abstract : Highly luminescent pure‐blue perovskite light‐emitting diodes (PeLEDs) are realized with (2‐(3, 6‐dichloro‐9 H ‐carbazol‐9‐yl)ethyl)phosphonic acid (36ClCzEPA) as multifunctional hole‐injection layer. With the synergetic effects of reduced hole injection barrier by strong interfacial dipole moment and interfacial passivation through the Pb–Cl electronic coupling, the PeLEDs reach a maximum external quantum efficiency of 4.80% at electroluminescence emission of 470 nm. For further details see article number 2201313 by BongSoo Kim, Jin Young Kim, and co‐workers.